Synthesis and characterization of kesterite Cu2ZnSn(SxSe1-x)4 thin films with low-cost for efficient solar cells - Aka Hyacinthe Aka; Amal Bouich; Boko Aka; Bernabé Mari Soucase (Results in Optics, 2023)
In this study, we conducted an investigation on the Cu2ZnSnS4 (CZTS) kësterite compound, which is considered an attractive material for its favorable absorption properties, making it a suitable semiconductor for photovoltaic applications. However, its market potential is limited by its low efficiency of 12.6%, primarily caused by the presence of secondary phases that act as recombination centers. Theoretically, the efficiency limit for CZTS ranges from 31% to 33%.To enhance the photovoltaic performance of CZTS, we employed a doping strategy by incorporating selenium (Se) into the Cu2ZnSn(SxSe1-x)4 film, where the sulfur-to-selenium ratio (S/Se) was optimized within the range of 0< x <1. The CZTS films were deposited onto FTO substrates using the spray pyrolysis technique, which is a simple and cost-effective method. The characterization of these films involved X-ray diffraction (XRD) and UV–visible spectroscopy analysis. Additionally, the morphology and topography of the CZTSSe layers were examined using scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. Transmission electron microscopy (TEM) was also employed.The results obtained in this study indicate that CZTSSe films exhibit band gap values ranging from 1.54 eV to 1.68 eV and grain compactness, with larger agglomerated grains on the film surface when the S/Se ratio is approximately 0.5 or lower. Moreover, the resistivity measurements revealed significant variations when sulfur and selenium were combined, suggesting the influence of their composition on the electrical properties of the CZTS films.